High Prevalence of Hookworm Species and Associated Factors among Soil-Transmitted Helminth-Infected Household Contacts in Burie Zuria District, Northwest Ethiopia: A Community-Based Cross-Sectional Study. (7th January 2023) - Assefa, Gedefaye; Alemu, Megbaru; Ayehu, Animen
Abstract : Background . Soil-transmitted helminths (STHs) are parasitic worms that are widely distributed in the tropical and subtropical regions. In Ethiopia, one of the tropical countries, STH infections are high and cause a huge burden. Several STH species show a pattern of household clustering with regard to prevalence and intensity. However, there is a scarcity of data on the status of STH infection among family contacts of STH-infected individuals in Ethiopia in general and in the study area in particular. Objective. This study is aimed at assessing the prevalence of soil-transmitted helminths and associated factors among STH-infected household contacts in Burie Zuria district, northwest Ethiopia. Method. A community-based cross-sectional study was conducted among 422 study participants from March to May 2021. Study participants were traced to their residences by following STH-infected patients. A convenient sampling technique was used to recruit the study participants. The stool samples were processed using duplicate Kato-Katz thick smears and a modified Ritchie's technique. The data were entered and analyzed using the Statistical Package for Social Sciences, version 26 of the software package. A P value <0.05 was considered a statistically significant association. Results. The overall prevalence of STHs was 36.5% (95% CI: 31.7%–41.5%). Two STHs, namely hookworm species (33.2%, 140/422) at (95% CI: 28.9%–37.8%) and Ascaris lumbricoides (4.3%, 18/422) at (95% CI: 2.7%–6.6%), were identified, with a double infection of 2.6% (4/154) at (95% CI: 1.0%–6.5%). Almost the majority (96.9%) of hookworm species and all Ascaris lumbricoides infections were categorized under a light intensity of infection. Family size >5 (AOR = 1.74 ; 95% CI: 1.15–2.60; P = 0.008 ) and lack of latrine facility (AOR = 1.86 ; 95% CI: 1.17–2.90; P = 0.02 ) were significantly associated with STH infections. Conclusion. A high prevalence of hookworms was found in the study area, where the majority of the study participants were adults. This finding may provide a basis for revising the school-based deworming programs that exclude the adult population. Public health interventions like accessing latrines, health education, and deworming programs should be regularly implemented for all age groups in the areas.